SCHEDULING TECHNIQUES IN PROBABILITY METHOD OF EVENTS THROUGH THE RADIO STAR - Samsul Samsul; Fitri Sjafrina., Ir, MMSI (Jurnal Sistem Informasi, 2000)
one of electronic media such as radio. Because broadcast radio plays an important role in both entertainment and educational information. One of Star Radio listeners who have a goal at age 25 to 35 years, requiring an accuracy in presenting the show, so listeners are not too bored. To support this, the technique and the method of probability and its supporting tools such as observation, interviews and questionnaires greatly affect the manufacturing schedule. Because the probability method is very help user program director, in determining the placement of a poet in accordance with the events provided to listeners. In order for event scheduling techniques can be used well, adding to the surveys through NGOs and the probability method used microsoft access applications. Because of the application, may minimize the problems in the manufacture of schedule. So that the resulting work process faster and more improved quality of Star Radio.